Safeguarding Personal Information: Communication Privacy Management By Gen-Z Influencers - Mutiara Cipta, Dessy; Alvin, Silvanus (International Journal of Educational Research & Social Sciences, 2023)
This research investigates the utilization of the NGL Link feature in Instagram Stories and its impact on the disclosure of personal information by micro-influencers. The study explores the experiences and privacy management strategies of Gen-Z micro-influencers. The study adopts a post-positivist paradigm and employs a case study approach to delve deeper into the research topic. Four micro-influencers meeting specific criteria were selected as informants for the study. Data collection techniques included interviews and data documentation. The informants shared their experiences, perspectives, and attitudes towards using the NGL Link feature. The findings reveal that the NGL Link feature enables micro-influencers to interact with their followers and share personal information, leading to increased engagement and deeper connections. However, concerns about privacy and the dissemination of personal information arise. The informants employ various filtering methods to protect their privacy, categorizing questions and selectively sharing responses. Dissemination of personal information by followers is observed, particularly among those who know the micro-influencer in real life. The study concludes that filtering serves as the primary privacy management strategy for micro-influencers using the NGL Link feature.